RESPONS PETANI TERHADAP SISTEM RESI GUDANG DI KABUPATEN BANTUL - , PRAJNA ADHI NUGRAHA; , Ir. Roso Witjaksono M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aimed to determine the farmer response toward warehouse receipt system and the influencing factors of it. From Bantul Regency, it was selected 3 districts namely sample purposively, which has been conducted socialization of warehouse receipt system (Bambanglipuro, Sedayu and Sewon). It takes 1 farmer group from each district sample purposively, which has been conducted socialization of warehouse receipt system. From each farmer group it was selected 20 members randomly, in order to obtain total of 60 respondents. Data were analyzed by using proportion test and multiple linear regression. The research results showed that most of farmer has a high response to warehouse receipt system. Factors affecting the farmer response to warehouse receipt system were farmerâs motivation and land ownership status